243 "WHAT DO OUR PATIENTS THINK?" CREATING A GERIATRIC INPATIENT QUESTIONNAIRE TO IDENTIFY PATIENTS' OPINION ON DELIVERY OF HOLISTIC CARE. (25th October 2022) - Walsh, J; Awadalla, R; Kovalshyn, V; Stankard, A; Cosgrave, N; NiBhuachalla, B; Mulroy, M
Abstract: Background: Our aim is to assess our patients' opinion on the delivery of key principles of Geriatric care in order to identify areas for improvement and change. The prevalence of delirium in frail older patients on inpatient wards is a major issue, the management of which includes a ward based multi-disciplinary approach. This holistic approach to patient care is our goal, however it is not clear whether the experience of our patients matches our aims. Methods: We developed a patient questionnaire consisting of 22 questions based on the core principles of good geriatric care. The survey included 3 questions on environment and privacy, 2 on mealtime, functional ability and assistance, 3 on continence management, 2 on mobility and rehabilitation, 6 on respect and autonomy, 2 on psychological and social aspects of care, 3 on pain and sleep, and 2 on safety and Covid-19. These questions also had a large degree of overlap in terms of core principles. We distributed the questionnaire prior to discharge in 3 different Geriatric care settings: one ward managing acute stroke with a majority of single rooms, one ward managing acute medical presentations with a majority of multi-occupancy bays and one ward in a non-acute hospital managing medical Geriatric patients undergoing rehabilitation. Results: Some key issues were identified by the survey: 60% identified issues with the ward environment and privacy, 100% did not wear a mask on the ward unless specifically asked to do so, 80% wore pyjamas or hospital gown for the majority of their stay, 40% reported issues in terms of respect and autonomy, 40% had issues with poor sleep due to external factors, 20% felt that they had insufficient time with rehabilitation. Conclusion: The survey was designed to assess the subjective experience of older inpatients, collecting qualitative data to highlight key areas of improvement to achieve holistic inpatient care.